Efektivitas Karang Jahe (Coral Chip) Dalam Penurunan Amoniak, Suhu, Dan pH Pada Limbah Cair Domestik Dengan Metode Biofilter Anaerob-Aerob dengan Media Karang Jahe - Saputra, M.Ardian; Yusmidiarti, Yusmidiarti; Mualim, Mualim (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Liquid waste that is not treated before being discharged into water bodies poses a risk to health, to the community and disrupts the environmental ecosystem. In general, domestic liquid waste is divided into two categories: black water and gray water. This study aims to determine the decrease in ammonia levels, temperature, and pH in domestic liquid waste after treatment with the anaerobic-aerobic biofilter method. This type of research is a pure experimental study (True Experiment) with a pretest-posttest design with a control group (pretest-posttest with control group). The pretest was carried out on both experimental groups, and after some time, the post-test was carried out, and the results were known as the effect of the treatment. Using the paired sample T-Test statistical test. The results of the measurements of ammonia, temperature, and pH of domestic liquid waste that have been carried out are then compared with the applicable standards based on the Regulation of the Minister of Environment and Forestry Number 68 of 2016 concerning Domestic Wastewater Quality Standards. The results of the study after treatment with the anaerobic-aerobic biofilter method of coral chip media in domestic liquid waste experienced a decrease in ammonia levels of 92.84% with an average of 0.07 mg / L, p = 0.000. While at a temperature level of 21.7% with an average of 29.9oC, p = 0.020 and at a pH level of 7.8% with an average of 8.3, p = 0.003. From the results of the study it can be concluded that there is a significant difference in the decrease in ammonia levels with a p-value (0.000) <0.005, There is a significant difference in the decrease in pH levels with a p-value (0.003) <0.005, there is no significant difference in the decrease in temperature levels because the p-value (0.020)> 0.005, this is because the temperature value at the time of the pre-test and post-test has an average of 30.30C which means it has met the ammonia level limit requirements. The conclusion of the study is that ginger coral (Coral Chip) in domestic liquid waste can reduce ammonia, temperature and pH levels. The research suggestion is that the results of the study can be used as a reference for further researchers Keyword : Domestic liquid waste;  anaerobic-aerobic biofilter;  ammonia;  temperature; pH